How Language Influences Conceptualization : From Whorfianism to Neo-Whorfianism = Kako jeziku utječe na koceptualizaciju : od whorfijanizma do neowhorfijanizma - Štrkalj Despot, Kristina (Array, 2021)
Do speakers of different languages think alike because of the universality of the experience of being human or do we all think differently because of differences in our languages? The answer to these questions has changed throughout the history of linguistic thought, ranging from observing languages merely as tools for expressing our thoughts to strongly believing that languages shape and even constrain our thoughts. This paper presents an overview of two most important theories that deal with these questions: the "rise and fall" of linguistic determinism (Whorfianism), and the development of its more cautious version – linguistic relativism (Neo-Whorfianism) – advocated today primarily within the framework of cognitive views of language, as well as their criticisms, most commonly within the framework of generative views of language.